2014
DOI: 10.5194/bgd-11-13251-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methane and carbon dioxide emissions from 40 lakes along a north–south latitudinal transect in Alaska

Abstract: Abstract. Uncertainties in the magnitude and seasonality of various gas emission modes, particularly among different lake types, limit our ability to estimate methane (CH4) and carbon dioxide (CO2) emissions from northern lakes. Here we assessed the relationship between CH4 and CO2 emission modes in 40 lakes along a latitudinal transect in Alaska to physicochemical limnology and geographic characteristics, including permafrost soil type surrounding lakes. Emission modes included Direct Ebullition, Diffusion, S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
114
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(128 citation statements)
references
References 87 publications
14
114
0
Order By: Relevance
“…Further study will be needed to assess whether the patterns observed here for ebullition CH 4 also apply to diffusive CH 4 fluxes. However, for the studied lakes, ebullition fluxes are estimated to be the dominant source of CH 4 emissions in the ice-free season (Jansen et al, 2019;Sepulveda-Jauregui et al, 2015).…”
Section: 1029/2019gl086756mentioning
confidence: 94%
“…Further study will be needed to assess whether the patterns observed here for ebullition CH 4 also apply to diffusive CH 4 fluxes. However, for the studied lakes, ebullition fluxes are estimated to be the dominant source of CH 4 emissions in the ice-free season (Jansen et al, 2019;Sepulveda-Jauregui et al, 2015).…”
Section: 1029/2019gl086756mentioning
confidence: 94%
“…, Sepulveda‐Jauregui et al. ). Erosion along thermokarst lake margins delivers this labile organic matter into anerobic lake bottoms, which promotes high rates of methane production and emission (Walter et al.…”
Section: Introductionmentioning
confidence: 99%
“…, Sepulveda‐Jauregui et al. ). Previous studies also highlight the importance of regional differences in hydrology and C chemistry across high latitude systems (McClelland et al.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the sample size, we also compared modeled concentrations to measurements of 30 encapsulated bubbles from four other thermokarst lakes in interior Alaska, the northern Seward Peninsula in Alaska, and northern Siberia (Walter et al, 2008;Sepulveda-Jauregui et al, 2014b). It was often impossible to classify ebullition sites beneath white ice during the spring ice-melt period as A, B, or C, so measurements from all ebullition classes were pooled and adjusted to account for observed differences in fresh bubble CH 4 concentrations among lakes (SepulvedaJauregui et al, 2014b).…”
mentioning
confidence: 99%